Passive battery thermal management and thermal safety protection based on hydrated salt composite phase change materials - Jingshu Zhang; Qian Liu; Xiaole Yao; Chen Sun; Xiaoqing Zhu; Chao Xu; Xing Ju (Energy Storage and Saving)
Lithium-ion batteries (LIBs) are progressing towards higher energy densities, extended lifespans, and improved safety. However, battery thermal management systems are facing increased demand owing to high-rate charging and discharging, dynamic operating conditions, and heightened thermal safety concerns. Therefore, this paper proposes a novel composite phase change material (CPCM) comprising Na2SO4–10H2O as the core phase change material (PCM) and expanded graphite as the thermal conductivity enhancer. The CPCM offers high latent heat, superior thermal conductivity, and a two-stage temperature control function for battery thermal management and safety. The optimal mass CPCM ratio, determined through comprehensive characterization and thermal property tests, resulted in a melting point of 29.05 °C, latent heat of 183.7 J·g−1, and high thermal conductivity of 3.926 W·m−1·K−1. During normal LIB operations, the CPCM efficiently absorbs and transfers heat, reducing the peak LIB temperature from 66 to 34 °C at 15 °C ambient temperature during a 3.7C high-rate discharge. Under dynamic conditions, the peak temperatures across the three cycles were consistently controlled at 36.7, 36.4, and 35.8 °C, respectively. In a thermal runaway state, the thermochemical heat storage of hydrated salt dehydration effectively slowed LIB temperature increase, delaying the time to reach 130 °C by 187 s. Suppression of the temperature rise outside the CPCM, combined with an extended dehydration plateau of up to 320 s, prevented the occurrence and propagation of thermal runaway in the battery.